Thermal and efficiency characterization of a low-backlash planetary gearbox: An integrated numerical-analytical prediction model and its experimental validation. (August 2016) - Concli, Franco
In the automation filed, low-backlash gearboxes are required to guarantee precise positioning. For such kind of applications, planetary speed reducers represent one of the most attractive solutions. This type of gearing ensures at the same time high power density and reduction ratios. On the other side, the compactness of the solutions leads to high operating temperatures. For this reason, it is important to be able to quantify the power dissipation and the operating temperatures already in the design stage, therefore to be able to find the best compromise between the load carrying capacity and the maximum transmittable power due to thermal limitations. For this reason, an innovative calculation method capable to quantify the efficiency under different operating conditions and the related operating temperatures was developed. Experimental tests were performed under different operating conditions to validate the predictions. The comparison shows good agreement.